Dampak Biaya Kuliah Tunggal Terhadap Kualitas Layanan Pendidikan - Sumarno, Sumarno; Gimin, Gimin; Nas, Syakdanur (Universitas Kristen Satya Wacana, 2017)
This study aims to determine the differences in the number of single tuition fees and non-single tuition; the proportion of resources and the allocation of funds before and after the single tuition policy; and the quality of educational services by single tuition and non-single tuition college students. The data was collected from students and leaders at the University of Riau through questionnaires, documentation, and interviews. Data were analyzed descriptively and different test. The results show that the amount of a single tuition fee is not much different from the non-single tuition fee. The proportion of funding sources from the public increased after a single tuition policy, but the proportion of allocations for operational costs decreased. Single tuition college students rated the quality of educational services lower than the non-single tuition of students with significant differences. Single tuition does not significantly affect the quality of education services.